PARTISIPASI ORANG TUA DAN GURU DALAM MEMBIMBING BELAJAR ONLINE PADA SISWA RA NURUL AKMAL KECAMATAN CIBITUNG - Ernawati, Ernawati; Nurlaeli, Acep (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
The purpose of this study was to describe the process of parents and instructors in helping students to study online at RA Nurul Akmal, Cibitung District. The qualitative research approach uses a case study methodology. Data collection methods included interviews, observations, and documentation, as well as descriptive data analysis. Data analysis techniques include data reduction, data display, and conclusion extraction. The results of this study indicate that (1) during the Covid 19 Pandemic, parental involvement in implementing learning at home must include helping and educating children as motivation. (2) The impact of parental involvement in learning at Nurul Akmal, Cibitung District during the Covid 19 pandemic is the promotion of family involvement in early childhood education at RA Nurul Akmal, Cibitung District.